2014
DOI: 10.1038/cddis.2014.422
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 and STAT3 repress BMF gene activity in colon cancer cells

Abstract: Histone deacetylase (HDAC) inhibitors are undergoing clinical trials as anticancer agents, but some exhibit resistance mechanisms linked to anti-apoptotic Bcl-2 functions, such as BH3-only protein silencing. HDAC inhibitors that reactivate BH3-only family members might offer an improved therapeutic approach. We show here that a novel seleno-α-keto acid triggers global histone acetylation in human colon cancer cells and activates apoptosis in a p21-independent manner. Profiling of multiple survival factors iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…reported [59] (Figure 2). BMF has an important function in the execution of apoptosis triggered by the metabolite methylselenopyruvate, which is an inhibitor of HDAC8 [60].…”
Section: Hdac8 and Diseasesmentioning
confidence: 87%
See 2 more Smart Citations
“…reported [59] (Figure 2). BMF has an important function in the execution of apoptosis triggered by the metabolite methylselenopyruvate, which is an inhibitor of HDAC8 [60].…”
Section: Hdac8 and Diseasesmentioning
confidence: 87%
“…smHDAC8 is the most abundant class I transcript, being expressed at high levels during almost all stages of the life cycle [69]. Transcript knockdown of smHDAC8 using RNAi in invasive [19,20,23,31,32,44,49,55,[57][58][59]; (B) muscle contraction [9]; and (C) entry of viruses [25]. (A) Representative molecular interactions of HDAC8 with crucial proteins in cancer.…”
Section: Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Although HDAC8 has been shown to promote growth of a number of cancer types (25), (37)(38)(39) and contribute to poor prognosis in childhood neuroblastoma (40), the molecular actions of HDAC8 in cancer remained poorly defined. Although specific HDACs can deacetylate nonhistone proteins (35), emerging data suggest that direct gene repression by HDAC8 might control key pathologic processes (41,42). Kang and colleagues have recently found that HDAC8 transcriptionally represses BMF, a Bcl-2 protein family member, to interfere BMF-mediated apoptosis in colon cancer cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…Although specific HDACs can deacetylate nonhistone proteins (35), emerging data suggest that direct gene repression by HDAC8 might control key pathologic processes (41,42). Kang and colleagues have recently found that HDAC8 transcriptionally represses BMF, a Bcl-2 protein family member, to interfere BMF-mediated apoptosis in colon cancer cells (42). Our present data demonstrate that HDAC8 acts in concert with EZH2 to epigenetically silence the Wnt antagonists AXIN2, NKD1, PPP2R2B, and PRICKLE1, leading to b-catenin activation and consequential cell proliferation.…”
Section: Discussionmentioning
confidence: 99%